Antibacterial Potential of Endemic Medicinal Plants of the Maluku Islands, Indonesia, against Urinary Tract Infection Pathogens - Astuty, Eka; Luhulima, Vinsa Delia; Ariwicaksono, Stefanus Cahyo (Folia Medica Indonesiana, 2024)
Highlights:1. Clove, cinnamon, and eucalyptus have found to be able to providing antibacterial agents for urinary tract infection (UTI).2. Ethanol extracts derived from clove leaves, cinnamon bark, and eucalyptus leaves can inhibit pathogenic bacteria responsible for UTI, indicating their potential as sources of bioactive compounds for UTI medication development. AbstractMedicinal plants possess antimicrobial properties that have been believed to be efficacious for treating various diseases. However, antimicrobial-based medicinal plants remain an untapped source of potential pharmaceuticals. This study aimed to evaluate the antibacterial properties of ethanolic extracts derived from several medicinal plants endemic to Maluku, Indonesia, specifically regarding their antibacterial activity against isolates of pathogenic bacteria found in the urine samples of urinary tract infection (UTI) patients. This was a true experimental research with a posttest-only control group design. The medicinal plant extraction was conducted using the maceration method. The pathogens were isolated using the dilution method. Following the pathogen isolation, the isolates were identified according to the colony morphology, Gram staining, and biochemical test results. The antibacterial activity was determined through the Kirby-Bauer disc diffusion test. The results indicated that five selected isolates (i.e., 0A1, 0A2, 0A3, 0A4, and 0A5) had a round shape with flat edges. Isolates 0A2 and 0A4 exhibited a solid white color, whereas isolates 0A1 and 0A3 displayed an off-white color, and isolate 0A5 showed a yellow color. Isolates 0A1, 0A2, and 0A4 were Gram-positive bacteria, while isolates 0A3 and 0A5 demonstrated Gram-negative characteristics. The biochemical testing revealed that the five selected isolates were identified as Staphylococcus warneri, Staphylococcus haemolyticus, Enterobacter aerogenes, Enterococcus faecium, and Escherichia coli. The ethanol extracts of clove (Syzygium aromaticum) leaves, cinnamon (Cinnamomum burmannii) bark, and eucalyptus (Melaleuca leucadendra) leaves demonstrated the ability to inhibit pathogenic bacteria responsible for UTI. Clove leaf ethanol extract exhibited the highest average clear zone compared to the other two ethanol extracts. This study concluded that medicinal plants from Maluku, Indonesia, the clove, cinnamon, and eucalyptus, have antibacterial potential that may be effective in treating UTI. Further investigation is necessary to fully comprehend the mechanisms of action, detection, and description of bioactive compounds, particularly against human pathogens.